Estudio de prefactibilidad para la instalación de una planta productora de aceite extraído a partir de semillas de mango - Córdova Córdova, Antonio Martín (2019)
The main objective of this research work is to determine the technical, environmental, economic-financial, social and market viability for the installation of an oil producing plant extracted from mango seeds. Through the different chapters included in the study, several key aspects that serve to understand and demonstrate the feasibility of the project are detailed.